Explicit and implicit knowledge with regard to the age of learners - Dubravac, Vildana (ExELL, 2013)
The present study set out to examine learners’ explicit and implicit foreign language knowledge with regard to their age. Therefore, two groups of learners from Zenica and Zavidovići (Bosnia and Herze-govina) presented the pool of informants in this study: 100 learners completing eight-year long primary school and 106 learners completing four-year long secondary school. The knowledge of four target structures (indefinite article, modal verbs, noun plural and adverb placement) was measured by means of three different tests: an oral elicited imitation test, a grammaticality judgement test and a metalinguistic test. The results indicate that the level of explicit and implicit knowledge varies with regard to the age of learners.